Asexuality and epistemic injustice: a gendered perspective - Cuthbert, Karen (Journal of Gender Studies, 2022)
Drawing on original qualitative research, I argue that the concept of ‘epistemic injustice’ proposed by the feminist philosopher Miranda Fricker, and located within a long genealogy of Black feminist scholarship, can be used sociologically to help understand the lived experiences of asexual people. I show how participants’ accounts of their asexual subjectivities were frequently denied, dismissed and over-written. However, I argue that these experiences were heavily gendered, in that asexual women were subject to epistemic injustices to a degree and in ways that their male counterparts were not, and that this must be understood within the power relations of hetero-patriarchy. These epistemic injustices revolved around old yet prevailing constructions of femininity and womanhood as ‘naturally’ asexual, passive, and lacking agency. When asexual men experienced epistemic injustice, this was rooted in familiar understandings of masculinity as necessitating an active and desiring sexuality. Using Fricker’s elucidation of hermeneutical and testimonial forms of epistemic injustice, I show how asexuality remains a culturally unfamiliar hermeneutical frame in a context of ‘compulsory sexuality’ but also how stories of asexuality are ‘heard’ based on the gendered (and unequal) distribution of testimonial credibility.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asexualité; cours; cycles supérieurs; discipline; europe; fem9000; injustices épistémiques; patriarcat; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; violences; études de genres

Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton classic editions, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

“Me Too”: Epistemic Injustice and the Struggle for Recognition - Jackson, Debra L. (Feminist Philosophy Quarterly, 2018)
Congdon (2017), Giladi (2018), and McConkey (2004) challenge feminist epistemologists and recognition theorists to come together to analyze epistemic injustice. I take up this challenge by highlighting the failure of recognition in cases of testimonial and hermeneutical injustice experienced by victims of sexual harassment and sexual assault. I offer the #MeToo movement as a case study to demonstrate how the process of mutual recognition makes visible and helps overcome the epistemic injustice suffered by victims of sexual harassment and sexual assault. I argue that in declaring “me too,” the epistemic subject emerges in the context of a polyphonic symphony of victims claiming their status as agents who are able to make sense of their own social experiences and able to convey their knowledge to others.
Keywords: #metoo; 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; harcèlement sexuel; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; philosophie féministe; périodes historiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éthique

Le sujet du féminisme est-il blanc? : femmes racisées et recherche féministe - Hamrouni, Naïma; Maillé, Chantal (Les éditions du remue-ménage, 2015)
À l’automne 2013, au moment de la controversée Charte des valeurs visant à interdire aux fonctionnaires le port de signes religieux dits ostentatoires, des femmes et des féministes se sont organisées. Pendant que certaines se regroupaient sous des bannières faisant de la laïcité la seule garante de l’égalité des sexes, des féministes se sont saisies d’espaces de parole alternatifs pour dénoncer le déni des droits fondamentaux et la stigmatisation des femmes issues de minorités. Si l’analyse des intersections entre racisme et sexisme fait partie intégrante du champ des études féministes depuis la fin des années 1960, le contexte politique récent ramène à l’avant-plan ces questions difficiles et nous force à les revoir sous un éclairage nouveau. Qui est le sujet-femme dont parle le féminisme? Qui fait partie de ce «Nous» et quelles femmes en sont implicitement tenues à la marge? Est-ce que les revendications au cœur du féminisme actuel représentent bien les préoccupations profondes des femmes minorisées, racisées? Compte tenu de l’effervescence que connaît le féminisme ces derniers temps, il était devenu incontournable de rassembler dans un même ouvrage ces réflexions sur le thème des femmes racisées, une première dans le monde francophone. Avec des textes de Leïla Benhadjoudja, Sonia Ben Soltane, Ryoa Chung, Julie Cunningham, Naïma Hamrouni, Gaëlle Kingué Élonguélé, Chantal Maillé, Ida Ngueng Feze, Geneviève Pagé, Sandrine Ricci, Karine Rosso et Diahara Traoré. Avec la participation de Alia Al-Saji, Alexa Conradi, Viviane Michel, Maria Nengeh Mensah et Geneviève Rail.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; cours; cycles supérieurs; fem1000; fem7000; femmes* racisées; intersectionnalité; lit2815; lit3220; lit3495; premier cycle; privilèges; périodes historiques; québec; racisme; régions géographiques; systèmes d'oppressions; études culturelles; études postcoloniales